Job Demands and Resources Shape the Risk of Burnout in Italian Child Neuropsychiatrists - Raspanti, Alessandra; Provenzi, Livio; Acampora, Marta; Borgatti, Renato; Millepiedi, Stefania; Mariani Wigley, Isabella L. C.; Barello, Serena (MDPI, 2025)
Objectives: To evaluate the influence of job demands and resources on burnout risk among Italian pediatric neuropsychiatrists.
Methods: This cross-sectional study was conducted between December 2023 and February 2024 and involved Italian pediatric neuropsychiatrists. The study applied the Job Demands-Resources (JD-R) model to assess the impact of job demands (such as work-family conflict, time pressure, and job uncertainty) and job resources (like organizational support and perceived job meaning) on burnout. Burnout was measured through emotional exhaustion, depersonalization, and personal accomplishment subscales. Demographic data, including gender and career stage, were analyzed for their association with burnout.
Results: High job demands were significantly associated with increased emotional exhaustion and depersonalization, while greater job resources correlated with lower burnout levels and higher personal accomplishment. Gender differences emerged, with female neuropsychiatrists reporting significantly higher emotional exhaustion and lower personal accomplishment than male neuropsychiatrists. Seniority was not a strong predictor, but early-career professionals, particularly residents, exhibited higher susceptibility to emotional exhaustion. Perceived job meaning and organizational support were protective factors across all burnout subscales, buffering the effects of job demands.
Conclusions: Burnout risk in Italian pediatric neuropsychiatrists is shaped by both job demands and resources. Addressing work-family conflict, job uncertainty, and time pressure alongside enhancing organizational support and fostering job meaning is crucial to mitigate burnout. Special attention should be given to early-career professionals and female neuropsychiatrists to reduce their emotional exhaustion and improve their well-being. These findings provide valuable insights for developing targeted strategies to improve well-being in this field, ultimately enhancing patient care.